TAKTIK EFEKTIF DALAM PROMOSI PROGRAM GERAKAN MASYARAKAT HIDUP SEHAT UNTUK MENDORONG PERUBAHAN PERILAKU DAN GAYA HIDUP - Dinda Sari Apriliani (CV. Adiba Aisha Amira, 2024)
Changes in people's lifestyles which tend to be physically inactive (for example spending a lot of time watching TV), low consumption of fruit and vegetables (eating lots of processed, ready-to-eat foods, high in sugar, salt, and consumption of cigarettes and alcohol). So that the risk of disease Non-Contagious (PTM) is getting higher. The health problems that arise today are the result of unhealthy lifestyle behavior such as smoking, not exercising regularly, not consuming vegetables and fruit as needed and never having regular check-ups at a health center. This research was carried out using literature techniques where data was taken from journals and articles that had gone through various screenings, including screening by ensuring the link between the title and the reference of the article used. a holistic and participatory approach is the key to success. This strategy includes public education, outreach campaigns, and the formation of healthy living habits. The integration of this program within the community structure is important to achieve sustainable results, showing that joint efforts between government, institutions and society are a crucial element in creating an environment that supports a healthy lifestyle.